2013
DOI: 10.3892/mco.2013.171
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography fluoroscopy-guided percutaneous 125I seed implantation for safe, effective and real-time monitoring radiotherapy of inoperable stage T1-3N0M0 non-small-cell lung cancer

Abstract: Abstract. The management of inoperable lung cancer remains a challenge. It has been proven that computed tomography (CT)-guided iodine-125 ( 125 I) seed implantation is a safe and efficient method for treating lung cancer. Computed tomographic fluoroscopy (CTF) is superior to traditional CT for percutaneous management of lung lesions, due to the real-time guidance and accurate localization of the lesions. The aim of the present prospective study was to evaluate the feasibility, safety and efficacy of CTF-guide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 24 publications
1
22
0
Order By: Relevance
“…The present study demonstrated an improved RR, LCR and 1-year OS compared with that of Zhang et al (30) due to the patients in the present study having early-stage NSCLC. These studies have demonstrated the good results of 125 I seed implantation for NSCLC (30)(31)(32). However, these studies all involved combination therapies of 125 I brachytherapy with chemotherapy or EBRT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study demonstrated an improved RR, LCR and 1-year OS compared with that of Zhang et al (30) due to the patients in the present study having early-stage NSCLC. These studies have demonstrated the good results of 125 I seed implantation for NSCLC (30)(31)(32). However, these studies all involved combination therapies of 125 I brachytherapy with chemotherapy or EBRT.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study indicated that 125 I brachytherapy may be used alone to improve the LCR, relieve the symptoms and prolong the OS time. Li et al (31) performed CT fluoroscopy-guided 125 I seed implantation for patients with stage T1-3N0M0 NSCLC and reported that at the median follow-up of 31.5 months, the LCR was 78.6% and the 1-, 2-and 3-year OS rates were 95.8, 78.0 and 55.0%, respectively. Another study reported that 125 I brachytherapy combined with chemotherapy was an effective treatment for inoperable stage III/IV NCSLC.…”
Section: Discussionmentioning
confidence: 99%
“…It has been used to study bone metastases [37] in mice and also has been applied to monitor the progression of lung and liver tumours [38,39,40]. …”
Section: Endometrial Cancer Pdx Modelsmentioning
confidence: 99%
“…The alternative is to implant radioactive seeds under the guidance of ultrasound, CT or laparoscope . The biological damage effects of CT‐guided radioactive seed implantation treatment are lower compared to the external irradiation …”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] The biological damage effects of CT-guided radioactive seed implantation treatment are lower compared to the external irradiation. 6,7 The CT has good spatial resolution and density resolution, which can accurately reveal the size, shape, position, necrotic cavity inside the lesion and the anatomic relationship with surrounding vessels of tumours. The CT is widely used in the diagnosis of malignant tumours and the assessment of the therapeutic effectiveness of 125 I seeds implantation.…”
Section: Introductionmentioning
confidence: 99%